Modified photo-electrochemical and photo-voltaic properties of solvothermally crystallised TiO2 nanotube arrays - Banki, Manmadha Rao; Tathavadekar, Mukta; Chunchu, Venkatrao; Roy, Somnath C. (Journal of Materials Science-Materials in Electronics, 2016)
TiO2 nanotube arrays formed by electrochemical anodization of Ti metal foil are crystallized through a solvothermal technique at 200 A degrees C (as compared to conventional annealing at 550 A degrees C), which results in anatase phase with granular morphology. The photo-current measurements reveal a higher current-density under the visible light for solvothermally crystallized samples. The photo-current behavior has been analysed and correlated with defect state characterization using X-ray photo-electron spectroscopy, Photo-luminescence, Electron paramagnetic resonance and Mott-Schottky measurements. These studies indicate an oxygen vacancy related defect state at 1.14 eV below the conduction band. Also, the density of defect states in solvothermally crystallised samples is an order of magnite, the photo-voltaic properties are studied through dye-sensitised solar cells. I-Vude higher than that in conventionally annealed samples. Furthermor characteristics of DSSC fabricated with solvothermally crystallised samples show comparable efficiency but higher dye-adsorption with respect to the conventionally annealed samples. Such a comparable efficiency at a lower thermal budget leads to reduced 'energy pay-back time' in solar cells fabricated with solvothermally crystallised TiO2 nanotube arrays. Finally, we demonstrate a proof-of-concept design of flexible solar cell based on TiO2 nanotubes grown on Kapton substrate and crystallised through the solvothermal technique.